Labor income responds differently to income-tax and payroll-tax reforms - Etienne Lehmann; François Marical; Laurence Rioux (Center for Economic Studies and ifo Institute (CESifo), 2012)
We estimate the responses of gross labor income with respect to marginal and average net-of-tax rates in France over the period 2003-2006. We exploit a series of reforms to the income-tax and payroll-tax schedules affecting individuals who earn less than twice the minimum wage. Our estimate for the elasticity of gross labor income with respect to the marginal net-of-income-tax rate is around 0.2, while we find no response to the marginal net-of-payroll-tax rate. The elasticity with respect to the average net-of-tax rate is not significant for the income-tax schedule, while it is close to -1 for the payroll-tax schedule. A plausible explanation is the existence of significant labor supply responses to the income-tax schedule, combined with sticky posted wages (i.e., the gross labor income minus payroll taxes divided by hours worked). Finally, the effect of the net-of-income-tax rate seems to be driven by participation decisions, in particular those of married women.
Keywords: H24; H31; J22; J38; 330; labor income; payroll tax; income tax; Lohnsummensteuer; Einkommensteuer; Steuertarif; Steuerwirkung; Einkommen; Arbeitsangebot; Schätzung; Frankreich